1991
DOI: 10.1007/bf01606063
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratin 13 in human epithelial neoplasms

Abstract: The distribution of the 52 kDa keratin 13 was evaluated immunohistochemically, using the AE8 monoclonal antibody. Various squamous and transitional cell epithelial lesions and representative control tissues were studied. This antibody performed adequately in formalin-fixed and paraffin-embedded tissue, but like keratin immunohistochemistry in general, required protease pretreatment. Keratin 13 was found consistently in the suprabasal layers of squamous epithelia of oral cavity, tonsils, larynx, esophagus, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…CK 13-deficient areas were quite extensive in some instances, prabably reflecting the loss of a suprabasal epithelial phe notype and the acquisition of the basal cell phenotype. This is in agreement with the findings of Malecha and Miettinen [26,27]. The sensitivity of CK 13 in detecting invasive malignancy and intraepithelial neoplasia may be useful for the differential diagnosis of difficult 'border line' cases.…”
Section: Cytokeratins In Cervical Lesionssupporting
confidence: 81%
“…CK 13-deficient areas were quite extensive in some instances, prabably reflecting the loss of a suprabasal epithelial phe notype and the acquisition of the basal cell phenotype. This is in agreement with the findings of Malecha and Miettinen [26,27]. The sensitivity of CK 13 in detecting invasive malignancy and intraepithelial neoplasia may be useful for the differential diagnosis of difficult 'border line' cases.…”
Section: Cytokeratins In Cervical Lesionssupporting
confidence: 81%
“…8, 30 Moll et al stated that a decrease in the CK13 expression was associated with an increase in the grade of malignancy in a transitional cell carcinoma. 31 Schaafsma also observed a decrease in the CK13 expression in higher-grade transitional cell carcinomas, particularly in the areas of muscle invasion.…”
Section: Discussionmentioning
confidence: 99%
“…CK13 is a differentiation-specific cytokeratin which is paired with cytokeratin 4 and expressed in normal oral squamous epithelia outside basal layers [11]. Ohkura et al [18] reported that CK13 expression levels were lower in oral squamous cell carcinoma and severe epithelial dysplasia than in mild and moderate epithelial dysplasia, and several additional studies have since reported that CK13 expression decreases with increasing severity of epithelial dysplasia [12,13,19].…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies have found significant relationships between malignancy and the expression levels of CK13 and CK17, indicating that combined assessment of CK13 and CK17 expression status might be a highly reliable diagnostic test to identify malignant transformation of oral epithelial dysplasia and oral squamous cell carcinoma [11,12,13,14,15,16,17,18,19,20]. However, it was previously unknown whether the expression status of CK13 or CK17 correlates with the morphological signs of atypia in superficial oral squamous cells collected by oral exfoliative cytology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation